Does the public receive and adhere to boil water advisory recommendations? A cross-sectional study in Newfoundland and Labrador, Canada. (December 2015) - Jones-Bitton, Andria; Gustafson, Diana; Butt, Kelly; Majowicz, Shannon
Abstract Background Highly publicized water supply problems highlight the importance of safe drinking water to the public. Boil water advisories (BWAs) are an important precautionary measure meant to protect public health by ensuring drinking water safety. Newfoundland and Labrador, Canada is a prime location for exploring public notification practices and adherence to recommendations as there were a total of 215 BWAs, affecting 6 % of the provincial population, in 145 communities between April 2006 and March 2007 when data for the present study were collected. Methods Residents who received household water from a public water supply were randomly selected for a telephone interview. Collected data included participants' notification of boil water advisory, satisfaction with information provided, and their adherence to recommendations. Results Most participants learned that a BWA had been issued or lifted in their community through radio, television, or word of mouth. BWAs were issued for a range of operational reasons. Almost all participants who had experienced a BWA reported wanting more information about the reasons a BWA had been issued. Low adherence to water use recommendations during a BWA was common. Conclusions This study is first to report on public adherence to boil water advisory recommendations in Canada. The findings raise public health concerns, particularly given the high number of BWAs issued each year. Further studies in partnership with community stakeholders and government decision-makers responsible for overseeing public water systems are needed to assess the perceptions of BWAs, the reasons for non-adherence, and to identify information dissemination methods to increase information uptake and public adherence with acceptable uses of public drinking water during a BWA.